Coalition Without Ideology: Political Motives of the Kebangkitan Bangsa Party (PKB) to Join the Indonesia Maju Coalition Post the 2024 Indonesian Elections - Subekti, Dimas; Sutan, Arissy Jorgi; Romadhon, Aditya; Al-Kautsar, Jefri; Anshori, M Wira (Universitas Riau Kepulauan, 2026)
This study examines the political motivations underlying the National Awakening Party’s (PKB) decision to join the Indonesia Maju Coalition following the 2024 presidential election by integrating insights from coalition theory, particularly office-seeking and policy-seeking frameworks, as well as party institutionalization theory. This research adopts a qualitative case study approach to uncover micro-level motivations through the analysis of multi-source data, including credible online news reports, official party documents, and elite public statements.The findings demonstrate that PKB’s realignment is not merely a general pragmatic shift but reflects a calculated balance between office-seeking and policy-seeking behavior. Empirically, PKB’s maneuver is evidenced by its targeted pursuit of strategic cabinet positions, indicating a structured effort to secure institutional access to executive power. At the same time, the study finds that PKB actively negotiates policy influence, particularly in socio-economic and religious-based welfare programs, to maintain alignment with its traditional voter base. Furthermore, the role of Muhaimin Iskandar is identified as a decisive factor, where leadership consolidation and personal political survival shape party strategy. The research also reveals that long-standing relational ties with Prabowo Subianto function as informal political capital, facilitating smoother coalition entry and reducing transactional costs. This study contributes to the literature by providing a micro-level empirical explanation of post-election coalition realignment in Indonesia, highlighting how ideological narratives are strategically embedded within pragmatic power calculations. Unlike previous studies that treat coalition shifts as purely opportunistic or structurally determined, this research demonstrates that PKB’s decision reflects a hybrid model of political behavior, where institutional interests, leadership agency, and policy aspirations interact simultaneously.